OPPRESSION, LITERATURE AND DIFFERING POINTS OF VIEW: . - Sebastian, Mrinalini (Journal of Dharma, 1991)
Why is image so central to a man's self-definition 7 Because all images, and especially created images represent a certain way of focussing on the world outside and therefore they represent a certain point of vievy. Now if we hold a certain point of view, we have automatically emphasized some aspects of reality, blocked out others, and glossed over the rest, and the image which we project or which we perceive is not objective reality but our own - or someone else's - reshaping of reality.